Quantitative evaluation of Parkinson's disease using sensor based smart glove - Niazmand, K.; Tonn, K.; Kalaras, A.; Fietzek, U. M.; Mehrkens, J. H.; Lueth, T. C. (2011 24th International Symposium on Computer-Based Medical Systems (CBMS), 2011)
Parkinson's disease (PD) is a chronic neurodegenerative movement disorder. The motor status of patients with PD can be characterized by the Unified Parkinson's disease rating scale (UPDRS). However, the UPDRS evaluates the movement disorders on a descriptive level only. Diagnosis and therapy of PD could be augmented if a quantitative assessment could be implemented. Thus, a wireless wearable sensor system for the evaluation of severity of motor dysfunction in PD was developed. The system was integrated into a smart glove. This glove has two touch sensors, two 3D-accelerometers and a force sensor to assess the cardinal motor symptoms of PD (bradykinesia, tremor and rigidity of hand and arm). In this paper we describe the setup of the glove and initial results.